Inovasi Pengolahan Sampah Organik Menjadi Ecoenzym: Solusi Multifungsi dalam Kehidupan Sehari-hari dan Pertanian - Isni Lailatul Magfiroh; Achmad Rizky Rifaldi Attamimi; Eka Wulan Ndari; Rizka Emilia Kirana; Umi Milatina Dziroh; Bunga Nanda Agustina (Lembaga Pengembangan Kinerja Dosen, 2026)
Organic waste is one of the major environmental problems caused by household activities. Improper waste management leads to environmental pollution and health risks. This community service activity aimed to educate and train the community in processing organic waste into ecoenzymes as a multifunctional and environmentally friendly product. The method used included socialization, training, and direct assistance to the community in producing ecoenzymes from fruit and vegetable waste through fermentation. The results showed that the community was able to understand the benefits and production process of ecoenzymes and began implementing them in daily life and agriculture. Ecoenzymes can be used as natural cleaning agents, plant fertilizers, and pest repellents. This activity contributes to reducing organic waste and improving environmental awareness and sustainable agriculture practices.